A Wide-Band Matching Method for Radio Frequency Coils Used in Soil Moisture Measurement - Jia-min WU; Yu-cheng HE; Zheng XU; Yan-he ZHU; Wen-zheng JIANG (Chinese Journal of Magnetic Resonance, 2021)
Accurate measurement of soil moisture is crucial in agricultural water management. A mini inside-out nuclear magnetic resonance (NMR) sensor has been designed to measure the moisture in model soils, consisting of three cylindrical magnets magnetized in the axial direction and four arc spiral coils with the same size in series. A circumferential symmetric constant gradient field can be obtained by adjusting the radius and height between the cylinders. To improve the signal-to-noise ratio of the sensor, this a wide-band matching method was proposed in this work to expand the excitation region of the radio frequency coils. The Carr-Purcell-Meiboom-Gill (CPMG) signal was analyzed through inverse Laplace transformation. With the results obtained, moisture content of the sample was found to be positively correlated with the integral area of T2 spectrum peak, verifying the feasibility of the sensor in soil moisture measurement.